Medicine science and dreams the making of physician-scientists - Schwartz, David A. (Springer, 2011)
Physician-scientists are unusual creatures. While we are drawn to the clinical challenges of our patients, we are also drawn to the opportunities that our patients' medical problems bring to science. This book contains the unique experiences and encounters that drew 21 accomplished physician-scientists to this profession. These personal stories are those of people and circumstances that have had profound effects on our career decisions, our creative opportunities, and our lives. These stories also serve to highlight the lessons learned along the way and the distinct attributes of these women and men of medicine and science. Our combined hope is that our collective biographies will enhance the public understanding of our profession, will move people from medicine to science and from science to medicine, and will inspire those who are contemplating this extraordinary profession.